Mechanical, chemical & flammability properties of ABS/PVC blends - Hashim, Shahrir; Hassan, Azman; Chew, Sau Yen (Universiti Teknologi Malaysia, 2003)
The first completely synthetic plastic, phenol-formaldehyde, was introduced by Baekeland in 1909, nearly four decades after Hyatt had developed a semisynthetic plastic-cellulose nitrate (Chanda and Roy, 1993). In 1927 poly(vinyl chloride) (PVC) and cellulose acetate were developed, and 1929 saw the introduction of urea- formaldehyde (UF) resins (Chanda and Roy, 1993). The development of new polymeric materials proceeded at an even faster pace after the war. Epoxies were developed in 1947, and acrylonitrile-butad iene-styrene (ABS) terpolymer in 1948 (Chanda and Roy, 1993). The next two decades saw the commercial development of a number of highly temperature-resistance materials. More recently, other new polymer materials were introduced, including several exotic materials which are mostly very expensive.